A flexibilização da terceirização ante o princípio constitucional da vedação ao retrocesso social - Sá, Yuri Kubrusly de Miranda (2021)
Research on the outsourcing of services in the 1988 constitutional text is of paramount importance for Brazilian society, given that the country goes beyond a political period of instability and changes, in which several changes in labor legislation have been carried out, aiming at easing labor rights, including the provision of services, a practice that was previously limited only by a summary understanding of the Superior Labor Court. With the publication of the Laws nº 13,429/17 and 13.467/17, the intermediation of labor was expanded, enabling its application in any activities of the service borrowing company, whether ancillary or main, a situation that raised the concern of jurists due to the possibility of precarious labor rights. Therefore, it is questioned whether the recent changes violate the implicit principle of prohibition against social retrogression, based on the protections of social rights, legal security and human dignity based on the Federal Constitution of 1988. Thus, the present study concluded that there are a devaluation of social labor rights, presenting its considerations on such an outcome. The methodology used in this article was developed through qualitative research, with exploratory and descriptive purposes, of bibliographic type, carried out in books, periodicals, dissertations, theses, jurisprudence and electronic sites.